Real Effects of Foreign Surplus Disposal in Underdeveloped Economies: Comment - Khan, Mahmood Hasan (Quarterly Journal of Economics, 1964)
Journal Article Real Effects of Foreign Surplus Disposal in Underdeveloped Economies: Comment Get access Mahmood Hasan Khan Mahmood Hasan Khan State Agricultural University, Wageningen, Netherlands Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 2, May 1964, Pages 348–349, https://doi.org/10.2307/1879335 Published: 01 May 1964